The Industrialization of Depressed Areas in Italy: Data and Commentary - Bozzola, G.B. (Relations industrielles / Industrial Relations, 1961)
SummaryThe Author casts some light upon the factors influencing the industrialization of Southern Italy, the economic and political problems raised by the phenomenon, and their consequences.